2008
DOI: 10.1163/156854008x354948
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of terrestrial Isopoda in the Berkoukech area, Kroumirie, Tunisia

Abstract: Until now, no investigations have been made on the diversity of woodlice in any region of Tunisia. In the framework of the "MEDCORE" project, particular emphasis has been put on the study of terrestrial isopod diversity in the Berkoukech area (north-west of Tunisia). Two sites were selected for this study: the beach dune system and an inland site located in Rabouet Bou Ali.In the beach dune system, isopods were studied in three biotopes: a grazed meadow (biotope 1), a maquis of Pistacia lentiscus, Quercus cocc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…The cosmopolitan species Porcellionides pruinosus (Brandt, 1833), characterised by a controversial taxonomic history and high ecological plasticity, exhibits geographical variations of its morphological features and its reproduction pattern. This species is highly synanthropic and is considered to be the most widely distributed species of terrestrial isopods (Vandel 1962;Garthwaite & Sassaman 1985;Michel-Salzat et al 2001;Lefebvre & Marcadé 2005;Achouri et al 2008). Originally native to Asia Minor (Vandel 1962) and carried extensively elsewhere by humans, P. pruinosus has colonised the entire world except the polar regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cosmopolitan species Porcellionides pruinosus (Brandt, 1833), characterised by a controversial taxonomic history and high ecological plasticity, exhibits geographical variations of its morphological features and its reproduction pattern. This species is highly synanthropic and is considered to be the most widely distributed species of terrestrial isopods (Vandel 1962;Garthwaite & Sassaman 1985;Michel-Salzat et al 2001;Lefebvre & Marcadé 2005;Achouri et al 2008). Originally native to Asia Minor (Vandel 1962) and carried extensively elsewhere by humans, P. pruinosus has colonised the entire world except the polar regions.…”
Section: Introductionmentioning
confidence: 99%
“…In Tunisia, the morphology (size and colour) of specimens from populations belonging to P. pruinosus varies with geographical locality and also changes with the bioclimatic levels, ranging from albinism to purplish blue (Achouri & Charfi-Cheikhrouha 2002). Furthermore, analyses using scanning electron microscopy and phenetic analysis have presented important phenotypic variations, and showed a polymorphism in some morphological characters such as the length of the antennae and the form of the pleotelson (Achouri & Charfi-Cheikhrouha 2005;Achouri et al 2008). Moreover, these populations exhibit different reproductive behaviours (Achouri & Charfi-Cheikhrouha 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Différentes (Achouri et al, 2008) ainsi que celle du parc national de Chambi (Khila et al, 2018). Egalement, cette richesse est légèrement moins importante que la richesse spécifique des isopodes terrestres des zones , 1954 ;Rushton and Hassall, 1987).…”
Section: Méthodologieunclassified
“…La diversité des oniscoïdes a été traitée en Europe (Orgiazzi et al, 2016) et quelques études ont été faites dans les pays de l'Afrique du Nord (Budde-Lund, 1885 ;Dollfus, 1896 ;Gadeau de Kerville, 1908 ;Monod, 1932 ;Paulian De Felice, 1939, 1942Shcmalfuss, 1989 ;Simon, 1885 ;Vandel, 1949). En Tunisie, plusieurs travaux de recherches portant sur la systématique et la répartition géographique des isopodes terrestres ont été réalisés dans le Nord et le centre : Berkoukech (Kroumourie) (Achouri et al, 2008), les agrosystèmes de la Medjerda (Fraj et al, 2010), les zones humides et côtières (Khemaissia et al, 2012(Khemaissia et al, , 2016 et dans certains parcs (Hamaied et al, en cours ;Khila et al, 2018).…”
Section: Introductionunclassified
“…Literature provides many studies about isopods diversity in the Mediterranean coastal wetland (e.g., Achouri et al 2008;Hamaïed-Melki et al 2011;Kemaissia et al 2012;Messina et al 2012); habitat preference (Vilisics et al 2007); but a few scientific studies on their plant communities preferences. Among these, David et al (1999) evaluated the relationship between diplopods and isopods and the vegetation structure in southern France; Sfenthourakis (1992); Sfenthourakis et al (2005Sfenthourakis et al ( , 2008 studied the habitat preference in natural areas in Greek mountains; Souty-Grosset et al (2008) reported the relationships among habitats, plant components and communities of terrestrial isopods in the Region Poitou-Charentes (France).…”
Section: Introductionmentioning
confidence: 99%